Protección del Dominio Público Marítimo-Terrestre Español. Aspectos procedimentales del Deslinde - Rojas Herrera, Oscar Miguel (2015)
This research develops a procedural aspect of the Delimitation of Maritime Public Domain in Spain in its various stages, as a protective action of the public domain. It takes place in two parts, the first of which acts of initiation of the procedure, such as the initiation and its effects, felling, precautionary measures and suspension of licenses. The second deals with other acts of development, completion and conclusion of the procedure.